Creating a Culture of Professional Development for Oncology Nursing in Asia - Myungsun Yi (Elsevier, 2016)
The importance of professional development of oncology nursing in Asia is growing along with growth in the cancer burden and disparity in cancer incidence and mortality between more- and less-developed regions, the latter of which includes most Asian countries. This paper proposes ways to advance the oncology nursing in terms of education, practice, and research in Asia. It also describes major challenges expected in developing and implementing a unique professional role for oncology nurses in Asia. This study will provide insights for Asian oncology nurses in developing culturally sensitive oncology nursing practices with limited health care resources.